Chitosan-ZnO Composite for Removal of Methylene Blue - Desnelli Desnelli; Leidya Yulinda; David Fernando; Fatma Fatma; Ady Mara (IJFAC (Indonesian Journal of Fundamental and Applied Chemistry), 2023)
This study aims to determine the effectiveness and increase in absorption of the chitosan-ZnO composite in the process of removing methylene blue when using the photodegradation method with the help of a UV lamp. Chitosan was synthesized from shrimp shell waste composite with metal oxide ZnO. The results of the characterization using XRD obtained the diffraction peak for chitosan at an angle of 2θ, namely 19.85°; 29.43°; 34.76° and chitosan-ZnO composite at an angle of 20.18°; 28.93°; 33.57° The SEM-EDX characterization shows that chitosan-ZnO has small, light-colored grains and more gaps and contains elements of chitosan and Zn. In the FTIR characterization, there was a decrease in intensity at a peak of around 3360 cm-1 which was caused by the chitosan-ZnO composite producing OH groups which reacted with methylene blue dye. In testing the effect of contact time using a UV lamp, there was an increase in the percentage of degraded methylene blue compared to without using a UV lamp. The maximum contact time is obtained at 60 minutes. While testing the effect of methylene blue dye concentration, the maximum absorption concentration was 45 ppm at 60 minutes of contact time. The adsorption capacity of the composite against methylene blue dye without UV light was 18.91 mg/g while using a UV lamp it increased to 20.145 mg/g. Based on this research, the chitosan/ZnO composite can be used quite well as a methylene blue dye remover.Keywords: Chitosan, Chitosan-ZnO, Photodegradation, Adsorption, Methylene blue.